Genetic Factors in Individual Predisposition toward Hemorrhagic Fever with Renal Syndrome - E. A. Tyugaeva; V. I. Korchagin; K. O. Mironov; A. E. Platonov (Эпидемиология и вакцинопрофилактика, 2019)
Hemorrhagic fever with renal syndrome (HFRS) is a zoonotic infection disease caused by Orthohantavirus which belongs to Hantaviridae family. This article is a brief review of recent data about genetic factors which play a role in individual predisposition toward HFRS. There are reports discovered associations of polymorphic sites with HFRS severity and risk complications. Polymorphic sites in genes which code proteins of immune (МНС, TNF, IL1) and endothelial (VE-cadherin) systems, blood coagulation (SERPINE1, ITGA2B, NOS) and detoxification (CYP1A1, GSTP1) systems and their links with disease are described in this article. HLA haplotypes B*08-DRB1*03 and B*46-DRB1*09, B*51-DRB1*09 are associated with severe forms of HFRS-PUUV and HFRS-HTNV respectively. TNF A-allele and AA-genotype in -308G>A SNP (rs1800629), CDH5 ТТ-genotype in 1550T>C SNP, SERPINE1 G-allele in -844A>G SNP (rs2227631), alleles HPA3 b, NOS2A*11 and NOS2A*11/NOS2A*12-genotype, CYP1A1 1А2С-genotype in SNP (rs1048943) and GSTP AG-genotype in SNP (rs1695) demonstrated associations with severe HFRS. Differences in the expression levels of GATA3, T-BET, CD3, IFNβ, NFkB, STAT1 and MxA genes in cell cultures stimulated by hantavirus. Expression of GATA3 was significantly higher in cell cultures of patients with severe HFRS than with a mild form. In contrast, MxA gene expression was up-regulated in cell cultures of patients with mild HFRS-PUUV. Considering individual genetic factors of HFRS patients would allow defining the best tactic of therapy and prophylaxis in this way. And as a result of applying this treatment in the clinical practice decrease of unfavorable disease outcome would occur.